Suboptimal Coherent Radar Detection in a KK-Distributed Clutter Environment. (14th October 2012) - Weinberg, G. V.
Abstract : The KK -Distribution is an important clutter model for high-resolution radar sea clutter returns obtained at X-band. The Neyman-Pearson optimal KK multilook detector has been derived recently, as well as the generalised likelihood ratio test suboptimal detector. Both these detectors are dependent on the modified Bessel-function of the second kind. This paper suggests a suitable suboptimal approach, using a well-known Bessel identity, eliminating the Bessel function dependence. This produces a computationally simpler detection scheme, whose performance is analysed using clutter parameters based upon real X-band radar returns.